2016
DOI: 10.1177/1933719115613449
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis Located Proximal to or Remote From the Uterus Differentially Affects Uterine Gene Expression

Abstract: The mechanisms that lead to the altered uterine gene expression in women with endometriosis are poorly understood. Are these changes in gene expression mediated by proximity to endometriotic lesions or is endometriosis a systemic disease where the effect is independent of proximity to the uterus? To answer this question, we created endometriosis in a murine model either in the peritoneal cavity (proximal) or at a subcutaneous remote site (distal). The expression of several genes that are involved in endometria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Our platform has one probe for HOXA10 at +1461, a different location, and shows intermediate methylation in controls and disease, and no differential methylation, thus accounting for the observed differences. Naqvi et al [49] used the Illumina platform and reported on 10 of 120 genes differentially methylated, and none of these 10 genes was in common with our data, potentially because of the use of samples from individuals with different severities of disease and/or different cycle phases, or, as they recently found, the distance of disease from the uterus [50]. Saare et al [33], as mentioned above, have shown similar genome-wide profiles between eutopic endometrium of disease and nondisease as those reported herein.…”
Section: Discussionmentioning
confidence: 53%
“…Our platform has one probe for HOXA10 at +1461, a different location, and shows intermediate methylation in controls and disease, and no differential methylation, thus accounting for the observed differences. Naqvi et al [49] used the Illumina platform and reported on 10 of 120 genes differentially methylated, and none of these 10 genes was in common with our data, potentially because of the use of samples from individuals with different severities of disease and/or different cycle phases, or, as they recently found, the distance of disease from the uterus [50]. Saare et al [33], as mentioned above, have shown similar genome-wide profiles between eutopic endometrium of disease and nondisease as those reported herein.…”
Section: Discussionmentioning
confidence: 53%
“…Subjects were participants in the Lifestyle and Fertility Study (ISIS Study), a prospective cohort study of healthy, nulliparous couples with no known infertility conditions, who were planning their first pregnancy (37). The overall objective of the study was to examine the association between antioxidant status and pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…Aberrant miRNA expression is a feature of many pathological conditions, including cancer, viral infections, metabolic diseases, and neurological disorders 8. In addition, there is growing evidence that miRNAs contribute to the pathogenesis of endometriosis by regulating abnormal cell differentiation, invasion, and inflammation 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%